Aplikasi Remote Sensing dan Geographic Information System untuk Pemetaan Potensi Obyek Daya Tarik Wisata di Desa Adat Batur Kecamatan Kintamani, Bangli - HARTATI TRI TUNGGAL JAYANTI; INDAYATI LANYA; I GUSTI PUTU RATNA ADI (Agrotrop : Journal on Agriculture Science, 2022)
Remote Sensing Application and Geographic Information System for Mapping Potential Tourist Attractions in Batur Traditional Village, Kintamani District, Bangli. Batur Village of Kintamani is the region defined as the National Tourism Strategic Area according to the Bali Provincial Regulation No. 16 of 2009. Batur Village consist of three Villages Department namely North, South, and the Central Batur Village. Not all Tourist Attraction are well-organized, as in the North Batur Village they don’t yet have a tourist attraction, different from the Central and South Batur Village of Mount Batur, Lake Batur and the Batur Temple has evolved and exist. The level of development of the tourism potential can be categorized to determine the factors supporting and inhibiting factors. Applications of Remote Sensing and GIS in the form of satellite worldview 1: 25.000 in 2020 Kintamani and software QGIS 3.10 was used as aims to update the database, mapping the location, the type attraction and the potential Tourism Attraction in the Village of Batur refers to the ACT No. 10 of 2009 in Article 7 as the four parameters (destination, industry, marketing and institutional) was weighted and score numerically and recommend strategies development of tourism in Batur Village. Based on the results 15 Tourist Attractions (TA) with 10 natural attractions, 2 religious tourism, 1 science tourism and 2 agro tourism located in Central and South Batur, there are 5 classes of potency (TA) very high, high medium, low and very low. The strategy, namely marketing with tour packages, makes WEBGIS to facilitate information for tourists who want to visit and provide regulations on abuse of buildings, landslides and pollution.